FM Based Localization: A Proposed Improvement - Khitam Abdulnabi Salman; Fatimah Abdulnabi Salman; Sami Hasan (Iraqi Journal of Science, 2021)
Localization is an essential issue in pervasive computing application. FM performs worse in some indoor environment when its structure is same to some extent the outdoor environment like shopping mall. Furthermore, FM signal are less varied over time, low power consumption and less effected by human and small object presence when it compared to Wi-Fi. Consequently, this paper focuses on FM radio signal technique and its characteristics that make it suitable to be used for indoor localization, its benefits, areas of applications and limitations.